2021
DOI: 10.1002/admi.202100850
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Collection in Non‐Fullerene Organic Solar Cells Using Iridium Complex as an Electron Extraction Layer

Abstract: Ultrathin iridium (Ir) complexes (e.g., bis[2‐(4,6‐difluorophenyl)pyridinato‐C2,N](picolinato)iridium(III) (FIrpic)) are first introduced as electron extraction layers (EELs) in non‐fullerene organic photovoltaics (OPVs), and a set of devices based on non‐fullerene materials is fabricated. It is demonstrated that this approach can rationally enhance the corresponding short current density and open circuit voltage and finally improve the photovoltaic performance of OPVs. Furthermore, optimized bilayer EELs usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For example, bis[2-(4,6-difluorophenyl)pyridinato-C2,N](picolinato) iridium(III) (FIrpic) is one of the most investigated blue phosphorescent material in the context of OLEDs. [26] Zhou et al combined FIrpic with 8-hydroxyquinoline lithium (Liq) and used them as the ETL. [26] The insertion of FIrpic facilitated the existence of interfacial dipole, provided more interfacial properties for exciton dissociation, charge extraction and ultimately enhanced the performance of PM6:Y6 based devices (15.75 %).…”
Section: Metal Chelatesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, bis[2-(4,6-difluorophenyl)pyridinato-C2,N](picolinato) iridium(III) (FIrpic) is one of the most investigated blue phosphorescent material in the context of OLEDs. [26] Zhou et al combined FIrpic with 8-hydroxyquinoline lithium (Liq) and used them as the ETL. [26] The insertion of FIrpic facilitated the existence of interfacial dipole, provided more interfacial properties for exciton dissociation, charge extraction and ultimately enhanced the performance of PM6:Y6 based devices (15.75 %).…”
Section: Metal Chelatesmentioning
confidence: 99%
“…[26] Zhou et al combined FIrpic with 8-hydroxyquinoline lithium (Liq) and used them as the ETL. [26] The insertion of FIrpic facilitated the existence of interfacial dipole, provided more interfacial properties for exciton dissociation, charge extraction and ultimately enhanced the performance of PM6:Y6 based devices (15.75 %). N719 is a popular dye used for dye-sensitized solar cells (DSSCs), which can also be used as ETL for OSCs.…”
Section: Metal Chelatesmentioning
confidence: 99%
See 1 more Smart Citation
“…126 It was reported that iridium (Ir) complexes could also be processed as CILs for regular OSCs, but the obtained PCE of 12.38% for the PM6:Y6 system was rather moderate. 127 Moreover, metallophthalocyanine and naphthalocyanine derivatives have also been designed to be used as CILs in OSCs with conventional structures. 128–130 These small molecules are alcohol soluble and processed on top of the photoactive layer, giving both high performance fullerene and non-fullerene OSCs.…”
Section: Coordination Complex Based Hybrid Cilsmentioning
confidence: 99%